DETERMINATION OF ANTHOCYANIN LEVEL IN KIDNEY BEAN (Phaseolus vulgaris L.) TEMPEH AS A HEPATOPROTECTIVE AGENT - Devina Ingrid Anggraini; Listiya Pramesti Mirantana (Jurnal Farmasi Sains dan Praktis, 2022)
Liver is a part of body that is used as a toxin neutralizer as well as a target for increasing free radicals. In counteracting free radicals, body needs antioxidants in one of the plant secondary metabolites, namely anthocyanins. Anthocyanins are organic compounds from the water-soluble flavonoid family that give red, blue, and violet colors. Fermentation can increase anthocyanin levels in kidney beans. This study aimed to determine the presence of anthocyanins in kidney bean (Phaseolus vulgaris L.) tempeh which can be used as a hepatoprotective agent and to determine the anthocyanin levels in kidney bean (Phaseolus vulgaris L.) tempeh. Qualitative analysis using HCl and NaOH with positive results showed the color change to solid red then to bluish green and then faded. Determination of total anthocyanin levels was carried out using UV-Vis spectrophotometric method with the pH differential principal in anthocyanin showed in mg/100gram sample at a maximum wavelength of 525.5 nm. The result was that the average anthocyanin content was 40.37mg/100gram with a variant coefficient is 0.325%.